2016
DOI: 10.1093/mnras/stw2594
|View full text |Cite
|
Sign up to set email alerts
|

The co-evolution of total density profiles and central dark matter fractions in simulated early-type galaxies

Abstract: We present evidence from cosmological hydrodynamical simulations for a co-evolution of the slope of the total (dark and stellar) mass density profile, γ tot , and the dark matter fraction within the half-mass radius, f DM , in early-type galaxies. The relation can be described as γ tot = A f DM + B for all systems at all redshifts. The trend is set by the decreasing importance of gas dissipation towards lower redshifts and for more massive systems. Early-type galaxies are smaller, more concentrated, have lower… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
113
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(146 citation statements)
references
References 100 publications
27
113
1
Order By: Relevance
“…According to Remus et al (2017), the mass growth of massive galaxies can be explained by two stages: 1) High redshift in situ mass growth resulting in a dense stellar component in the center of the potential where the dark matter fraction is low, 2) dry merger events dominate the mass growth at lower redshift (with major mergers being rare) resulting in the build-up of a stellar envelope increasing the half-light radius and thus the dark matter fraction (similar to the interpretation above). 6.4.…”
Section: Stellar-to-dynamical Mass Evolutionmentioning
confidence: 99%
“…According to Remus et al (2017), the mass growth of massive galaxies can be explained by two stages: 1) High redshift in situ mass growth resulting in a dense stellar component in the center of the potential where the dark matter fraction is low, 2) dry merger events dominate the mass growth at lower redshift (with major mergers being rare) resulting in the build-up of a stellar envelope increasing the half-light radius and thus the dark matter fraction (similar to the interpretation above). 6.4.…”
Section: Stellar-to-dynamical Mass Evolutionmentioning
confidence: 99%
“…Napolitano et al 2009;Deason et al 2012;Alabi et al 2016). However, recent models built on cosmological hydrodynamic simulations (Wu et al 2014;Remus et al 2017;Lovell et al 2018) notably predict shallower trends with mass for f DM at the fiducial 5r e . The range of expected values from the Magneticum simulations (Remus et al 2017) in particular is indicated by the dashed lines in Fig.…”
Section: Dark Matter Fraction Within 5r Ementioning
confidence: 97%
“…Contemporary cosmological hydrodynamic models (e.g. Remus et al 2017;Lovell et al 2018) predict that within 1r e the ratio of DM to total mass f DM ranges over ∼ 0.2 to 0.7 for large galaxies and is also a strong function of redshift. A higher in situ fraction of stellar mass should go along with lower f DM , while a larger fraction of dry merging (accretion) should extend the stellar mass profile and increase the inner f DM .…”
Section: Dark Matter Fraction Within 5r Ementioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 3 we show the derived dark matter fractions within 5 R e vs galaxy stellar mass from our analysis ) [7] and two sets of cosmological simulations. The simulations are with (Remus et al 2017) [8] and without (Wu et al 2014) [9] AGN feedback. The plot also shows a simple galaxy model based on galaxy scaling relations and an NFW dark matter halo.…”
Section: Dark Matter Contentmentioning
confidence: 99%